2004
DOI: 10.3200/jmbr.36.1.91-103
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prehension Between 5 and 10 Years of Age: Distance Scaling, Grip Aperture, and Sight of the Hand

Abstract: The authors investigated whether 5- to 10-year-old children (N = 75) differ from adults (N = 12) in the developmental course of distance scaling and the adaptations to the inability to see the hand during prehension movements. The children reached under a surface and grasped and lifted an object suspended through it. All children scaled velocity appropriately for movement distance, both with and without sight of the hand. However, 5- to 6-year-old children did not increase grip aperture with increased distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…While reaching and grasping (prehension) is one of the earliest developing motor skills in humans, this skill undergoes a prolonged developmental trajectory, becoming more and more refined through childhood and adolescence (Kuhtz-Buschbeck et al, 1998; Schneiberg et al, 2002; Smyth et al, 2004). Although no longitudinal studies have investigated the developmental trajectory of reaching and grasping in ASD during childhood and adulthood, case-control studies suggest that atypicalities in reach to grasp movements appear to persist past infancy.…”
Section: Introductionmentioning
confidence: 99%
“…While reaching and grasping (prehension) is one of the earliest developing motor skills in humans, this skill undergoes a prolonged developmental trajectory, becoming more and more refined through childhood and adolescence (Kuhtz-Buschbeck et al, 1998; Schneiberg et al, 2002; Smyth et al, 2004). Although no longitudinal studies have investigated the developmental trajectory of reaching and grasping in ASD during childhood and adulthood, case-control studies suggest that atypicalities in reach to grasp movements appear to persist past infancy.…”
Section: Introductionmentioning
confidence: 99%
“…But how does perception of affordances for fitting through openings progress from infants' rudimentary body scaling to adult-like accuracy? Despite a wealth of studies on the kinematics of reaching (Berthier, 2011; Hay, 1979; Kuhtz-Buschbeck, Stolze, Jöhnk, Boczek-Funcke, & Illert, 1998; Schneiberg, Sveistrup, McFadyen, McKinley, & Levin, 2002; Smyth, Katamba, & Peacock, 2004) and locomotion (Assaiante, 1998; Assaiante, Woollacott, & Amblard, 2000; Cowie, Atkinson, & Braddick, 2010; Ledebt, Bril, & Breniere, 1998) in children, relatively little is known about children's perception of affordances for fitting. One recent exception demonstrated that 8- to 10-year-olds scaled decisions to turn their shoulders to fit through openings based on opening size (Wilmut & Barnett, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been suggested that children need more time to process and use visual and proprioceptive feedback information when reaching to grasp, as expressed in increased time spent in deceleration (Pryde et al, 1998). However, Smyth et al (2004) demonstrated that 5-to 6-year-old children do not necessarily rely more on visual information than do older children and adults, or spend longer time in deceleration, when reaching. In the present study, the increased time to establish a grip in the FM condition indicates that the timing and anticipatory control of the reach-to-grasp movements were affected.…”
Section: Discussionmentioning
confidence: 93%